BAGAIMANA START-UP DAPAT BERTAHAN? PERAN KEWIRAUSAHAAN STRATEGIS DAN KAPABILITAS AMBIDEXTERITY UNTUK MENCAPAI KINERJA BISNIS - Nabila Kharimah Vedy; Sri Rahayu; Evi Novitasari (STMIK Pringsewu, 2022)
Organizational learning is a learning activity in administrative processes through interaction with the environment that encourages organizations to integrate knowledge better. Through a series of strategies, the development of organizational learning needs to be carried out to provide a competitive advantage for the organization. This study offers strategic entrepreneurship and Ambidexterity capabilities to achieve business performance, which is recognized concepts that can improve business performance, and create competitive advantages for companies and businesses. With the increasing development of technology, companies need to consider ambidexterity capabilities to maintain their competitive edge. Where companies can exploit and explore the opportunities they have to generate innovation and achieve business performance, especially new businesses such as start-ups.